Prevalence and Impact of Rheumatologic Pain in Cystic Fibrosis Adult Patients - Schmoll, Axelle; Launois, Claire; Perotin, Jeanne-Marie; Ravoninjatovo, Bruno; Griffon, Muriel; Carré, Sophie; Mulette, Pauline; Ancel, Julien; Hagenburg, Jean; Lebargy, François; Deslée, Gaëtan; Salmon, Jean-Hugues; et al. (Frontiers in Medicine, 2022)
Background: With the improvement of cystic fibrosis (CF) patient survival, the prevalence of long-term complications increased, among them rheumatologic disorders. Methods: The objective of this prospective study was to evaluate the prevalence of spinal and joint pain, and their impact on disability, anxiety, depression, and quality of life in CF adult patients. Results: Forty-seven patients were analyzed, 72% of men, mean aged 27.7 years, with a mean body mass index of 21.8 kg/m² and a mean FEV1% of 63%. Twenty-two patients (47%) described rheumatologic pain either spinal (n=15, 32%) and/or joint pain (n=14, 30%). Patients with spinal and/or joint pain were smaller (p=0.022), more frequently colonized with Staphylococcus aureus (p<0.008), had more frequent F508 homozygous mutations (p=0.014), and more impairment of the 6-minute walking distance (p=0.04). The presence of rheumatologic pain was associated with anxiety and with 3 domains of the CFQ 14+scale. Compared with patients with no pain or, spinal or joint pain only, patients with both spinal and joint pain exhibited a more pronounced impact on the Health Assessment Questionnaire (HAQ), anxiety and several domains of the quality of life scales (SGRQ, CF14+, MOS SF- 36). Conclusion: Rheumatologic pain is frequent in CF adult patients, and affects daily living, anxiety and quality of life. Systematic assessment of rheumatologic pain should be included in the management of CF patients. Trial registration: The study was registered on ClinicalTrials.gov (NCT02924818) on 5th October 2016.